‘EDICTUM DOMITIANI DE PRIVILEGIIS VETERANORUM’. EDYKT CESARZA DOMICJANA O PRZYWILEJACH WETERANÓW - Świętoń, Adam; Tadajczyk, Konrad (Zeszyty Prawnicze, 2016)
‘Edictum Domitiani de Privilegiis Veteranorum’: The Emperor Domitian’s Edict on Veterans’ Privileges Summary This article contains the text and translation of the Edictum Domitiani on veterans’ privileges with a commentary. This edict is an interesting illustration of imperial military and social policy on the privileges of veterans and their families. Its text survives thanks to a private copy made by Marcus Valerius Quadratus, a discharged soldier of the legio X Fretensis. The privileges granted by the Emperor Domitian guaranteed benefits also found in other veterans’ concessions (as the diplomata militaria shows) – citizenship, tax exemption, conubium with a peregrine woman. But the personal scope of Domitian’s privileges is unusual – its beneficiaries were not only veterans and their children, but also their wives and parents (if they lived with the soldier after his discharge). The full range of privileges is unknown; unfortunately Valerius’ copy is partly damaged. The authors also discuss some of the doubts concerning the edict’s addressees and types of privileges granted under this edict. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />